Coherence or dissonance in the international framework : a shifting paradigm : proceedings of a workshop of the G-24 (OPEC Fund for International Development ViennaAT, 2001)
Focuses on five main areas within the institutional framework of the international organizations viz. overlapping responsibilities; overriding jurisdictions; non-state actors and global governance; regional monetary arrangements for developing countries; and accountability, governance and reform in the international financial institutions (IFIs).
Keywords: INSTITUTIONAL FRAMEWORK